2018
DOI: 10.5194/angeo-36-1303-2018
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent processes in the Earth's magnetotail: spectral and statistical research

Abstract: We use the magnetic field measurements from four spacecraft of the Cluster-II mission (three events from 2005 to 2015) for the analysis of turbulent processes in the Earth's magnetotail. For this study we conduct the spectral, wavelet and statistical analysis. In the framework of statistical examination, we determine the kurtosis for selected events and conduct extended self-similarity evaluation (analysis of distribution function moments of magnetic field fluctuations on different scales). We compare the high… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 69 publications
(75 reference statements)
1
12
0
Order By: Relevance
“…Non‐self‐similar scaling of PDFs of the fluctuations in the flow or magnetic field was used to identify intermittent turbulence (Weygand et al, ). The magnetic fluctuations in the plasma sheet were found to be consistent with expectations for an intermittently turbulent MHD fluid (Kozak et al, ; Weygand et al, ). Stepanova et al () found that the PDF of the PC index (polar cap index charactering the energy supply from the solar wind into the magnetosphere) could be fitted by two log‐normal distributions.…”
Section: Discussionsupporting
confidence: 78%
“…Non‐self‐similar scaling of PDFs of the fluctuations in the flow or magnetic field was used to identify intermittent turbulence (Weygand et al, ). The magnetic fluctuations in the plasma sheet were found to be consistent with expectations for an intermittently turbulent MHD fluid (Kozak et al, ; Weygand et al, ). Stepanova et al () found that the PDF of the PC index (polar cap index charactering the energy supply from the solar wind into the magnetosphere) could be fitted by two log‐normal distributions.…”
Section: Discussionsupporting
confidence: 78%
“…The solar wind and the magnetosphere are high Reynolds number plasma environments [45], both showing scaleinvariant dynamics and power-law PSDs. Several studies have been carried out to investigate the turbulent nature of the solar wind (e.g., [32,36]; and references therein) and the magnetosphere (e.g., [46][47][48][49][50][51]) separately, invoking turbulence and a SOC approach to describe the dynamics of the two plasma environments, respectively. At this stage, an obvious question arises: whether SOC is different from turbulence.…”
Section: Discussionmentioning
confidence: 99%
“…It must be noted, however, that beside the strong connection existing between the solar wind and the magnetosphere via reconnection processes, the solar wind and the magnetosphere are both high Reynolds number plasmas [45]. As a result, we would expect that not only the solar wind but also the magnetosphere shows a scale-invariant dynamics and powerlaw PSD (e.g., [46][47][48][49][50][51]). On the other hand, geomagnetic indices are widely used to study the magnetospheric output and are indicative of the most important magnetospheric current systems.…”
Section: Scale-invariant Dynamics Of the Solar Wind And The Magnetospmentioning
confidence: 99%
“…A main focus of this study is the spectral characteristics of severe magnetic fluctuations associated with field dipolarization in the near-Earth magnetotail. Compared with previous spectral studies (e.g., Kozak et al, 2018;Shiokawa et al, 2005) associated with field dipolarization, the present study was focused on severe magnetic fluctuations defined as B ∕B > 0.5. Then, as explained in section 2, the signature of dipolarization was used to clarify the timing of substorm onsets.…”
Section: Discussionmentioning
confidence: 99%
“…Ono et al (2009) showed that these magnetic fluctuations can induce an electric field that further accelerates ions nonadiabatically. Previous studies have also reported the spectral properties of these magnetic fluctuations (e.g., Kozak et al, 2018;Lui et al, 1992;Nishitani & Oguti, 1988;Ohtani et al, 1998;Shiokawa et al, 2005). The Active Magnetospheric Particle Tracer Explorers/Charge Composition Explorer (AMPTE/CCE), Spacecraft Charging at High Altitude (SCATHA), and GEOTAIL satellites used in those studies provided magnetic field measurements at ∼8.8, ∼7.8, and 8-11 R E , respectively.…”
Section: Introductionmentioning
confidence: 99%